2021
DOI: 10.1111/joim.13354
|View full text |Cite
|
Sign up to set email alerts
|

Increased fracture risk after discontinuation of anti‐osteoporosis medications among hip fracture patients: A population‐based cohort study

Abstract: R et al. Increased fracture risk after discontinuation of anti-osteoporosis medications among hip fracture patients: A population-based cohort study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 35 publications
(46 reference statements)
0
9
0
1
Order By: Relevance
“…An additional analysis undertaken to assess the potential for residual confounding associated with BMD and BMI found that both variables were balanced between the two study arms at baseline, therefore mitigating the concern of residual confounding due to inability to include these parameters as part of the PS matching in the primary analysis. Another residual confounder could be an increased fracture risk in the off-treatment cohort due to rebound bone resorption after denosumab discontinuation [ 32 ]. However, this potential confounder is unlikely as it has been shown that rebound of bone turnover is absent in subjects receiving a single injection of denosumab [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…An additional analysis undertaken to assess the potential for residual confounding associated with BMD and BMI found that both variables were balanced between the two study arms at baseline, therefore mitigating the concern of residual confounding due to inability to include these parameters as part of the PS matching in the primary analysis. Another residual confounder could be an increased fracture risk in the off-treatment cohort due to rebound bone resorption after denosumab discontinuation [ 32 ]. However, this potential confounder is unlikely as it has been shown that rebound of bone turnover is absent in subjects receiving a single injection of denosumab [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our nationwide population-based cohort study also showed discontinuation of Dmab resulted in an increased risk of major osteoporotic and vertebral fractures. The increased risk tended to reveal within 1 year after discontinuation and the risk was greater among the patients with longer duration of Dmab treatment (11). In addition to vertebral fractures, higher incidences of major osteoporotic fractures and hip fractures were also observed in the following years of Dmab withdrawal (12).…”
Section: Introductionmentioning
confidence: 95%
“…
We have carefully read the cohort study by Fu et al on anti-osteoporosis medication (AOM) [1]. The authors reported that persistent anti-osteoporosis drug users have a lower risk of major fractures compared with patients who discontinued the treatment.
…”
mentioning
confidence: 99%
“…A better understanding of the relation between the discontinuation of AOM and fracture risk can help improve clinical medication usage. The authors took into account several variables to minimize the bias such as hospital accreditation level, duration between index admissions, and selected comorbidities [1]. Nevertheless, we still identified a few potential confounders.…”
mentioning
confidence: 99%